An Index to book reviews in the humanities. (Detroit P. Thomson, 1997)
Annual, 1963-, Quarterly, with an annual cumulation, 1960-62.
Keywords: Humanities -- Book reviews -- Indexes; Books -- Reviews -- Indexes